The Imposibles Band : Characteristic of Musical Form - Matthayomnan, Jirat; Pikulsri, Chalermsak; Charanyananda, Anak (Journal of Fine and Applied Arts Khon Kaen University, 2020)
This research aims to study the characteristics of musical form The Impossibles band By using qualitative research methods for data collection Both from documents and interviews By using the musicology process and anthropology are used to analyze specific characteristics musical form. The results were as follows : The Impossibles Band Has continued to develop music since its founding in 1966 until the band's dissolution in 1976, with the influence of music from many bands in western country including The Beatles , The Rolling Stone, Ray Conniff, Engelbert Humberdinck, Perry Como, Dean Martin, Every Brother, Chicago and Santana. The composition of the music is distinctive in Harmony, chord and rhythm that is the unique . There has been a change in the use of various chords such as minor, b5th, 9th , #9th , 11th , maj7, dim, sus which has not yet appeared of the bands in Thailand in that era. The Impossibles band is therefore the incipient in the development of modern Thai song in Thailand.